Pharmacokinetics of Lactobacillus plantarum NCIMB 8826, Lactobacillus fermentum KLD, and Lactococcus lactis MG 1363 in the human gastrointestinal tract - VESA, T; POCHART, P; MARTEAU, P (Alimentary pharmacology & therapeutics, 2000)
Objectives: Genetically modified lactic acid bacteria may be a way to deliver vaccinal epitopes in the gastrointestinal tract. Aim: Three strains of lactic acid bacteria were studied for their pharmacokinetics in the human gastrointestinal tract. Methods: The survival of the strains was studied up to the ileum in six subjects each, after ingestion of 150 g of fermented milk. The strains and their concentrations in the products were Lactobacillus fermentum KLD (107 cfu/g), Lactobacillus plantarum NCIMB 8826 (108 cfu/g), and Lactococcus lactis MG 1363 (108 cfu/g). Ileal fluid was aspirated by intestinal intubation and immediately cultured. L. plantarum NCIMB 8826, which was found in high concentrations in the ileum, was studied for its survival in the faeces after consumption of 150 g of fermented milk three times daily for 7 days. Faecal samples were collected for culture. Results: The concentration of L. plantarum NCIMB 8826 in the ileum reached 108 cfu/mL after a single dose, with a survival of 7%. L. fermentum KLD and Lc. lactis MG 1363 had lower (0.5 and 1.0%, respectively) and shorter (4 h) survival in the ileum. During the 7‐day ingestion period, L. plantarum NCIMB 8826 reached high concentrations (108 cfu/g) in the faeces, with a survival of 25 ± 29%. None of the strains colonized. Conclusions: L. plantarum NCIMB 8826 has a promising pharmacokinetic profile as a candidate vaccine vehicle.